Does the Covid-19 Have an Impact on the Insurance Industry? A Non-Parametric Approach to Takaful and Conventional Insurance in Indonesia - As-Salafiyah, Aisyah (SMART Insight, 2023)
This study aims to see the efficiency level of insurance companies, especially general insurances in Indonesia, both Islamic insurance (known as takaful) and conventional insurance using nonparametric approach. The study period of this study was five years from 2016 to 2020, especially highlighting the year of 2020, when the COVID-19 pandemic spread in Indonesia, and whether it impacts the insurance companies. The findings of this study indicate that the average efficiency score of Sharia and conventional insurance in Indonesia from 2016 to 2020 has fluctuated differently, with conventional insurance decreasing and sharia insurance increasing following a dip. This may explain why COVID-19 has had little effect on the insurance business. COVID-19 has a detrimental impact on the efficiency of conventional insurance but does not affect Islamic insurance, according to the DEA research. Additionally, this study classifies the improvement potential for each input and output variable.